Approaches and distances between Costa Rica and the Cuban Revolution: Some relations of hostility and deference - Barrera-Rivera, Dan Abner (2022)
The article discusses how political ties between some governments in Costa Rica and Cuba have been since the triumph of the Cuban Revolution on January 1, 1959. Tensions, estrangement, and approximations between the two countries are shown. These relationships were conditioned by exacerbated anti-communism in the context of the Cold War and remained several years later. It is noted that, in all this time, the influence and interests of the United States were present in the relationships of these nations. Political (and personal) approaches that are not always recorded when talking about the links between these countries are taken into account. For this purpose, each government’s official statements and assertions regarding diplomatic ruptures and restorations in five decades are critically analyzed; it is also investigated in testimonial sources, videos and newspaper articles of some of the protagonists. They are two nations with different political regimes that, despite discordant situations, approaches, and collaborations prevailed over the sowing and cultivation of anti-communism